2019
DOI: 10.1002/jcb.28622
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA CASC11 promotes cancer cell proliferation in bladder cancer through miRNA‐150

Abstract: Long noncoding RNAs (lncRNAs) CASC11 is an oncogenic lncRNA in gastric cancer and colorectal cancer. Our study aimed to investigate the role of lncRNA CASC11 in bladder cancer. In this study we showed that plasma lncRNA CASC11 was upregulated, while plasma miRNA‐150 was downregulated in patients with early‐stage bladder cancer than in healthy controls. Altered expression of plasma lncRNA CASC11 and miRNA‐150 separated patients with bladder cancer from healthy controls. lncRNA CASC11 expression was inversely co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 24 publications
2
74
0
Order By: Relevance
“…The transcription factor c-Myc represses miR-129-5p expression in hepatocellular carcinoma ( Han et al, 2016 ). Overexpression of lncRNA CASC11 promotes bladder cancer cell proliferation via inhibition of miR-150 expression ( Luo et al, 2019 ). The mechanisms by which miR-16-1-3p is repressed in breast cancer require to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor c-Myc represses miR-129-5p expression in hepatocellular carcinoma ( Han et al, 2016 ). Overexpression of lncRNA CASC11 promotes bladder cancer cell proliferation via inhibition of miR-150 expression ( Luo et al, 2019 ). The mechanisms by which miR-16-1-3p is repressed in breast cancer require to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical assay showed that the expression of LINC00662 in BC tissues was negatively correlated with the 5-year survival rate of the patients. LncRNA can absorb specific miRNA by sponge effect or competitively bind miRNA to regulate the binding of endogenous miRNA to its target gene 26 . In this study, we predicted and validated the possible interact target of LINC00662.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of lncRNAs to the growth, proliferation and survival of different types of cancer has been studied ( 36 , 46 , 79 83 ) Several studies have emphasized the potential of lncRNAs in promoting metastasis in breast cancer cell lines and tissues ( 84 , 85 ). Dysregulation of lncRNA inhibiting proliferation and metastasis ( NLIPMT ) has been reported to enhance growth and metastasis in breast cancer tissue.…”
Section: Role Of Lncrna In Breast Cancermentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are RNA molecules in the range of 200–2,000 bp ( 32 ). lncRNAs have been found to play a crucial role in the development of various cancer types, including breast ( 33 ), thyroid ( 34 ), renal ( 35 ), colorectal ( 36 ), prostate ( 37 ) and ovarian cancer ( 38 ), and have been reported to interact with various molecules during transcription, chromosome remodeling, cellular trafficking and translation ( 39 ). In addition, lncRNAs serve regulatory roles during transcription, mRNA processing, maturation of mRNAs, modification of histone complexes and DNA methyltransferase modifications that occur during epigenetic regulation ( Fig.…”
Section: Introductionmentioning
confidence: 99%